Students’ achievement of the 21st century skills in the process of teaching and learning biology among science students - Rahmania Pamungkas; Hadi Suwono; Herawati Susilo; I. Ibrohim; Muhammad Saefi; Reni Marlina; Tri Maniarta Sari (JPBI (Jurnal Pendidikan Biologi Indonesia), 2023)
Nearly one in five pupils in OECD nations do not possess the fundamental knowledge and abilities necessary to get by in today's communities (OECD, 2019), which is a sign of exclusion. There is an unfairness in that students from low socioeconomic origins are twice as likely to be low performers, suggesting that social or personal factors prevent them from fulfilling their educational potential. This study intends to investigate the achievement of the 21st Century Biology Skills Test (21CBST) and to compare it to students’ level of socio-economic status. The result (TIMSS) (2015) revealed that Indonesian students failed to achieve minimum standards in Science and Mathematics, with 33.3% achievement in science and 35% in mathematics for content domain and 33,3% in the cognitive domain. Comprising 37 multiple choice items, the 21st Century Biology Skills Test (21C-BST) includes representatives from five domains which are; i) Digital Age Literacy, ii) Inventive Thinking, iii) Effective Communication, iv) High Productivity, and v) Religion, Health and Civic. The respondents comprised 210 form students who took biology subject in school. The study revealed that students from high socio-economic status scored higher than their counterparts from low socioeconomic status. This paper concludes with some practical suggestions for improving students’ 21st-century skills, particularly within the context of biology teaching and learning.